2021
DOI: 10.1080/21645515.2021.1883379
|View full text |Cite
|
Sign up to set email alerts
|

Burden of severe bronchiolitis in children up to 2 years of age in Spain from 2012 to 2017

Abstract: Bronchiolitis represents a heavy burden of disease in children under 2 years of age in our society due to the high infectivity of the Respiratory Syncytial Virus [RSV] and the vulnerability of the youngest children. The objective of this retrospective epidemiological study was to show the burden of severe bronchiolitis in Spain through population-based estimates of hospitalizations due to bronchiolitis in children up to 24 months old during a 6-year period (2012)(2013)(2014)(2015)(2016)(2017). A total of 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 36 publications
8
22
1
Order By: Relevance
“…Findings from this study confirm findings from previous studies identifying that, despite the relatively low RSV-associated ICU admission rates, the rate of RSV-related manifestations remains high [ 18 , 23 , 39–41 ]. The trend for bronchiolitis decreasing with age corresponds with previous findings, as bronchiolitis is a leading cause of hospitalization in children aged <2 years [ 19 , 20 , 25 , 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Findings from this study confirm findings from previous studies identifying that, despite the relatively low RSV-associated ICU admission rates, the rate of RSV-related manifestations remains high [ 18 , 23 , 39–41 ]. The trend for bronchiolitis decreasing with age corresponds with previous findings, as bronchiolitis is a leading cause of hospitalization in children aged <2 years [ 19 , 20 , 25 , 34 ].…”
Section: Discussionsupporting
confidence: 88%
“…Young age is a known risk factor for RSV infection, with about 45% of hospital admissions and in-hospital deaths due to RSV-related bronchiolitis occurring in children younger than 6 months [ 17 , 35 ]. Previous studies have shown that the highest incidence of childhood hospitalization for bronchiolitis in Spain in the last 20 years occurred during the first year of life, particularly among children aged 0–2 months, estimated at about 4000 cases per 100,000 children under 12 months of age; rates decrease significantly thereafter [ 19 , 36 ]. Estimates published for different countries around the world are variable, probably due to different healthcare settings and estimation methods, and to the different underlying characteristics of the study populations [ 21 , 37 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of pediatric hospital discharges for respiratory diseases to which a generic diagnostic code is assigned, e.g., bronchitis or bronchiolitis, has been addressed previously. In a recently published study [ 36 ], we collected data from all patients who had been assigned a generic diagnostic code for bronchiolitis, assuming that 50–80% of cases were caused by RSV infection. In this study, however, the patients were analyzed in different groups based on whether the diagnosis code was generic or specifically RSV-positive.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, studies often include only RSV-specific and/or acute bronchiolitis diagnosis codes—or RSV confirmed cases when laboratory data is available—approaches which are expected to widely underestimate the number of RSV cases, due to lack of systematic testing and coding [ 10 12 ]. On the other hand, most studies focus on hospitalizations, leaving outside substantial direct healthcare burden from outpatient visits [ 7 , 13 15 ]. In United States, a study found the incidence of RSV cases in the outpatient setting to be over thirty times higher than the incidence of hospitalizations [ 7 ].…”
Section: Introductionmentioning
confidence: 99%